Holistic or Biologic Dentistry : Future Alternative or Not - Sudakshina Mukherjee1 , N. Aravindha Babu2 , E. Rajesh3, K.M.K.Masthan4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Holistic dentistry is also called Progressive dentistry, biologic dentistry, or biocompatible dentistry. Holisticdentistry is a new alternative branch of traditional dentistry where it deals with the unrecognized impactof oral health on the overall health of the person. This new idea of dentistry strongly opposes some ofthe treatment modalities of traditional dentistry. Although the concept and practise has brought about arevolution but some of the complementary methods followed by holistic dentists under criticism.